Elementos de interoperabilidade na perspectiva da catalogação descritiva - Castro, Fabiano Ferreira de; Santos, Placida L. V. A. C. [UNESP] (Universidade Federal de Campina Grande, 2014)
In the digital informational environment, currently, where various kinds of resources coexist with shapes and patterns of heterogeneous metadata, many efforts have been made to achieve interoperability in order to use multiple metadata standards and reuse the metadata records through the development strategies, ranging from simple mappings between metadata elements to modeling complex structural. The intensive use of Information and Communication Technologies (ICT) generates the development of a various possibility of metadata standards, essential in environments manipulation of bibliographic data. The objective is to point out to what extent the methods of Descriptive Cataloging, explicit codes of cataloging (AACR2 and RDA) and metadata standards, favor the design model of digital informational environments for better structured information retrieval. For this purpose, a methodology of analysis of the exploratory and descriptive literature with the study of scientific production of the main area of Information Science and Librarianship, it is possible to identify and understand the major technological changes in the heart of Descriptive Cataloging in the digital scope. As a result is presented a proposal for modeling a functional requirements of digital informational environments that ensure interoperability in the bibliographic domain. It is believed that the use of metadata, ontologies and the theoretical and methodological foundations of Descriptive Cataloging, once articulated, can redesign options to new informational environments, whether in the modeling of the bibliographic catalogs, or in the form of representation of information resources, ensuring interoperability.

Atualmente, no ambiente informacional digital, onde vários tipos de recursos coexistem com formatos e padrões de metadados heterogêneos, muitos esforços têm sido feitos para alcançar a interoperabilidade, a fim de utilizar vários padrões de metadados e de reutilizar os registros de metadados, através do desenvolvimento de estratégias, que vão desde os simples mapeamentos entre elementos de metadados à modelagem estrutural complexa. O uso intensivo das Tecnologias da Informação e Comunicação (TIC) gera o desenvolvimento de uma gama de padrões de metadados, instrumentos fundamentais nos ambientes de manipulação de dados bibliográficos. Objetiva-se apontar em que medida as metodologias da Catalogação Descritiva, explicitadas nos códigos de catalogação (AACR2 e RDA) e nos padrões de metadados, favorecem o delineamento modelar de ambientes informacionais digitais melhor estruturados para a recuperação da informação. Para tanto, com uma metodologia de análise exploratória e descritiva do tema, com o estudo das principais produções científicas da área de Ciência da Informação e da Biblioteconomia, é possível identificar e compreender as principais mudanças tecnológicas no cerne da Catalogação Descritiva, no âmbito digital. Como resultado apresenta-se uma proposta de requisitos funcionais para a modelagem estrutural de ambientes informacionais digitais, que garantem a interoperabilidade no domínio bibliográfico. Acredita-se que a utilização dos metadados, das ontologias e dos fundamentos teóricos e metodológicos da Catalogação Descritiva, uma vez articuladas, podem redesenhar novas opções aos ambientes informacionais, seja na modelagem dos catálogos bibliográficos, ou ainda, na forma de representação dos recursos informacionais, garantindo a interoperabilidade.
Interoperability's elements in the perspective descriptive cataloging
Keywords: Metadata standards; Descriptive cataloging; Interoperability; Structural modeling of digital informational environments; Information and technology; Padrões de metadados; Catalogação descritiva; Interoperabilidade; Modelagem estrutural de ambientes informacionais digitais; Informação e tecnologia